Physics of IED Blast Shock Tube Simulations for mTBI Research - Mediavilla Varas, Jesus; Philippens, M.; Meijer, S.R.; van den Berg, A.C.; Sibma, P.C.; van Bree, J.L.M.J; de Vries, D.V.W.M. (Frontiers in Neurology, 2011)
Shocktube experiments and simulations are conducted with a spherical gelatin filled skull-brain surrogate, in order to study the mechanisms leading to blast induced mild traumatic brain injury (mTBI). A shocktube including sensor system is optimized to simulate realistic improvised explosive devise (IED) blast profiles obtained from full scale field tests. The response of the skull-brain surrogate is monitored using pressure and strain measurements. Fluid-structure interaction (FSI) is modeled using a combination of computational fluid dynamics (CFD) simulations for the air blast, and finite element (FE) model for the structural response. The results help to understand the physics of wave propagation, from air blast into the skull-brain. The presence of openings on the skull and its orientation does have a strong effect on the internal pressure. A parameter study reveals that when there is an opening in the skull, the skull gives little protection and the internal pressure is fairly independent on the skull stiffness; the gelatin shear stiffness has little effect on the internal pressure. Simulations show that the presence of pressure sensors in the gelatin hardly disturbs the pressure field.